Effects of growth and starvation conditions on bacterial adhesion to plastic surfaces - He Lei; Qin Jianmei; Rong Haifeng; Tong Meiping (National Science Open)
The effects of nutrient conditions on the formation of plastisphere were unclear. This study investigated the impacts of growth and starvation conditions on the adhesion of both Gram-negative and Gram-positive bacteria to six plastics in both salt solution and river water. We found that bacteria grown in nutrient-rich condition (LB) contained higher adhesion capability to all six plastics than those grown in nutrient-restricted condition (M9). Starvation process yet decreased bacterial adhesion to plastics under all examined solution conditions. Via deep investigation of the respective contribution of bacterial shape, motility, flagella, and extracellular polymeric substances (EPS) particularly its overall amount, functional groups, major components together with their corresponding secondary structure, as well as its hydrophobicity, the mechanisms driving to the different adhesion capability of bacteria onto plastics subjected to varied nutrient conditions were systemically determined. We found that the enhanced hydrophobicity of bacteria grown in LB contributed to the greater bacterial adhesion to six plastics than those grown in M9. While the changed bacterial shape, the reduced bacteria motility, loss of flagella, and the reduced hydrophobicity of EPS resulted from the change of the composition of proteins and monosaccharides all contributed to the reduced bacteria adhesion to plastics after starvation process. This study indicated that the formation of plastisphere in environment could be greatly influenced by the nutrient condition for bacterial survival, which would affect the environmental risks of plastics.